Comparative clinical characteristics and outcomes of patients with community acquired bacteremia caused by Escherichia coli, Burkholderia pseudomallei and Staphylococcus aureus: A prospective observational study (Ubon-sepsis). - Ranjani Somayaji (Public Library of Science (PLoS), 2021)
Background Community acquired bacteremia (CAB) is a common cause of sepsis in low and middle-income countries (LMICs). However, knowledge about factors associated with outcomes of CAB in LMICs is limited. Methodology/principal findings A prospective observational study (Ubon-sepsis) of adults admitted to a referral hospital with community-acquired infection in Northeastern Thailand was conducted between March 1, 2013 and February 1, 2017. In the present analysis, patients with a blood culture collected within 24 hours of admission that was positive for one of the three most common pathogens were studied. Clinical features, management, and outcomes of patients with each cause of CAB were compared. Of 3,806 patients presenting with community-acquired sepsis, 155, 131 and 37 patients had a blood culture positive for Escherichia coli, Burkholderia pseudomallei and Staphylococcus aureus, respectively. Of these 323 CAB patients, 284 (89%) were transferred from other hospitals. 28-day mortality was highest in patients with B. pseudomallei bactaeremia (66%), followed by those with S. aureus bacteraemia (43%) and E. coli (19%) bacteraemia. In the multivariable Cox proportional hazards model adjusted for age, sex, transfer from another hospital, empirical antibiotics prior to or during the transfer, and presence of organ dysfunction on admission, B. pseudomallei (aHR 3.78; 95%CI 2.31-6.21) and S. aureus (aHR 2.72; 95%CI 1.40-5.28) bacteraemias were associated with higher mortality compared to E. coli bacteraemia. Receiving empirical antibiotics recommended for CAB caused by the etiologic organism prior to or during transfer was associated with survival (aHR 0.58; 95%CI 0.38-0.88). Conclusions/significance Mortality of patients with CAB caused by B. pseudomallei was higher than those caused by S. aureus and E. coli, even after adjusting for presence of organ dysfunction on admission and effectiveness of empirical antibiotics received. Improving algorithms or rapid diagnostic tests to guide early empirical antibiotic may be key to improving CAB outcomes in LMICs.